STUDY ON THE MECHANICAL AND PHYSICAL PROPERTIES OF VACUUM BAGGING OF GLASS FIBRE-REINFORCED EPOXY COMPOSITE - AHMAD KHAIRUL, AHMAD FAIDHIARIF (2018)
Glass fibre is a material that is made up of the various fine fibre of glass. The glass fibre has high stiffness and strength that can be used for fabrication purpose. The reason of the study is due to lack of research on how the glass fibre reinforced epoxy been made by using vacuum bagging process. On top of that, previous research is lacking of data regarding the mechanical and physical properties of the fabrication process that had be used. Therefore, the study will focus on the evaluation of the effect processing parameter of vacuum bagging on the glass fibre reinforced epoxy composite properties. The procedure that had considered is by preparing the equipment which is woven glass fibre and the mixture of epoxy with the hardness for hand layup as step one. Thus, the vacuum preparation had made after the first step. After the preparation had been made, vacuum process will start by putting the specimen in the vacuum and seal it using the tape that will ensure the pressure inside the bag will not same with outside pressure. Moreover, the vacuum pump will run and ensure the pressure of inside and outside will not at the same state by looking at the pressure gauge. After the vacuum bagging has been done, the specimen then had cured at room temperature for 24 hours. For more variable of the parameter, the author has set a post-curing process which is the specimen had put in the oven for a heating between the different temperature at 120 minutes. The quality characterisation test had been run by using the Universal Tensile Machine (UTM) for tensile and bending tests. In addition, the result showed that a high number of layer and post-curing temperature give a better data and result. Thus, the contribution of both processing parameter can be more than 50% to the baseline. The higher number of layer and post-curing temperature gives the higher numerical number of data in term of Tensile Strength and Flexural Stress and Strain.